Changing Tides: sculpting heterogeneity through exposing and submerging form in tidal pool design - de Villiers, Roché (School of Architecture, Planning and Geomatics, 2021)
This project highlights the dynamic processes, systems and ecological interactions of the intertidal landscape. The tidal pool sits at this intersection of land and water, known as the intertidal zone. They are site specific social spaces where people can interact with marine life and they are valuable public places that can connect people to nature. As such it's in the unique position to raise awareness about the dynamism of natural systems and ecological processes which can be particularly well observed in tidal flux. In the context of climate change and associated sea level rise this awareness of change and flux will be particularly important in fostering adaptation capabilities. Although tidal pool design respond to site in their engineering and are mostly built on rocky substrates, I have noticed that not much form inspiration is drawn from the unique geologies of tidal pool sites. As a result the natural heterogeneity and delight inherent in rock pools is lost and somewhat mono-functional human-centered spaces result. As a design strategy, I considered the core importance of specificity to site as a strategy to build in this rather unusual landscape. The intent is to find and establish a new set of criteria for tidal pool design within the Table Mountain Sandstone geology. In this thesis I'm exploring whether the process of designing with intimate attention to the host rocks can provide better opportunities and a more sensitive approach for creating heterogeneity in tidal pool design that make vibrant space for both social and ecological functions. Sculpting heterogeneity in the rocky intertidal zone of St. James' rocky outcrop will enhance the cohabitation of human and marine life and hold the opportunity to celebrate the ecological value of this rich and sensitive environment through environmental education through experience.